1998
DOI: 10.1111/j.1399-6576.1998.tb05292.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sevoflurane on intracranial pressure, cerebral blood flow and cerebral metabolism: A dose‐response study in patients subjected to craniotomy for cerebral tumours

Abstract: Sevoflurane is a cerebral vasodilator in patients with cerebral tumours. Sevoflurane increases CBF and decreases CVR in a dose-dependent manner. CO2-reactivity is preserved during 1.5% and 2.5% sevoflurane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(38 citation statements)
references
References 38 publications
2
35
1
Order By: Relevance
“…Four studies assessed CVR-CO 2 on the ipsilateral side of the cerebral pathology and found that reactivity was preserved during sevoflurane, isoflurane, and desflurane anesthesia. 36,38,40 One study found no differences in CVR-CO 2 between the normal and abnormal hemispheres in patients with brain tumors with isoflurane (1 MAC) or propofol (4 mg/kg/h) anesthesia. 41 Another study found that CVR-CO 2 was maintained in both the normal and abnormal hemisphere in patients undergoing AVM resection under isoflurane anesthesia.…”
Section: Intracranial Pathologymentioning
confidence: 98%
See 1 more Smart Citation
“…Four studies assessed CVR-CO 2 on the ipsilateral side of the cerebral pathology and found that reactivity was preserved during sevoflurane, isoflurane, and desflurane anesthesia. 36,38,40 One study found no differences in CVR-CO 2 between the normal and abnormal hemispheres in patients with brain tumors with isoflurane (1 MAC) or propofol (4 mg/kg/h) anesthesia. 41 Another study found that CVR-CO 2 was maintained in both the normal and abnormal hemisphere in patients undergoing AVM resection under isoflurane anesthesia.…”
Section: Intracranial Pathologymentioning
confidence: 98%
“…Six studies assessed the CVR-CO 2 in patients undergoing craniotomy for tumor removal 36,[38][39][40] or arteriovenous malformation (AVM) resection. 37 The CVR-CO 2 testing was performed after induction of anesthesia, before surgical incision.…”
Section: Intracranial Pathologymentioning
confidence: 99%
“…Although inhalational agents do result in cerebral vasodilatation and are therefore likely to increase intracranial pressure, this is only a significant problem if the fraction of volatile agent used is high (i.e. > 1 MAC approx) [13][14][15]. Finally, the vast majority of respondents (90%) do not know that a rapid increase in the concentration of desflurane may be associated with sympathetic stimulation and hypertension [16].…”
Section: Discussionmentioning
confidence: 94%
“…On the negative side, although several studies have shown that isoflurane does not alter ICP, Talke et al found that 0.5-1 MAC sevoflurane significantly increased cerebrospinal fluid (CSF) pressure in normocapnic patients who had no mass effect (19)(20)(21).…”
Section: Effects Of Sevoflurane and Isoflurane On Brain Injury 115mentioning
confidence: 98%